A reconstituted system reveals how activating and inhibitory interactions control DDK dependent assembly of the eukaryotic replicative helicase - Herrera, M. Carmen (Nucleic Acids Res, 2015)
During G1-phase of the cell-cycle the replicative MCM2–7 helicase becomes loaded onto DNA into pre-replicative complexes (pre-RCs), resulting in MCM2–7 double-hexamers on DNA. In S-phase, Dbf4-dependent kinase (DDK) and cyclin-dependent-kinase (CDK) direct with the help of a large number of helicase-activation factors the assembly of a Cdc45–MCM2–7–GINS (CMG) complex. However, in the absence of S-phase kinases complex assembly is inhibited, which is unexpected, as the MCM2–7 double-hexamer represents a very large interaction surface. Currently it is unclear what mechanisms restricts complex assembly and how DDK can overcome this inhibition to promote CMG-assembly. We developed an advanced reconstituted-system to study helicase activation in-solution and discovered that individual factors like Sld3 and Sld2 can bind directly to the pre-RC, while Cdc45 cannot. When Sld3 and Sld2 were incubated together with the pre-RC, we observed that competitive interactions restrict complex assembly. DDK stabilizes the Sld3/Sld2–pre-RC complex, but the complex is only short-lived, indicating an anti-cooperative mechanism. Yet, a Sld3/Cdc45–pre-RC can form in the presence of DDK and the addition of Sld2 enhances complex stability. Our results indicate that helicase activation is regulated by competitive and cooperative interactions, which restrict illegitimate complex formation and direct limiting helicase-activation factors into pre-initiation complexes.